'A distinct family likeness': A Reappraisal of the Creative Partnership between Anne and Emily Brontë. (2nd July 2020) - Quinnell, James
Abstract : Since the publication of Charlotte Brontë's 'Biographical Notice of Ellis and Acton Bell' as an appendage to the 1850 edition of Wuthering Heights and Agnes Grey, scholarship on Anne Brontë has been shackled to biography in ways perhaps not realized. Ideas of Anne as the quiet one, less able to cope with exposure to the harshness of the world as her sisters, have diluted the impact of her writing. This is particularly the case in her relationship with Emily, where Anne has lost out to the supposed wilder Romanticism of her elder sibling. Moreover, the commonplace idea that Anne became Emily's critic in the publication of their novels has further served to sunder them. I argue for the continued affinity of thought between Emily and Anne in the period their novels were written and published. Charlotte's 'Biographical Notice' has profoundly affected the way that Anne is seen in relation to Emily and vice versa. I use Emily's Belgian devoirs to help tease out, via Agnes Grey, how the two were still as much twins in the way they saw the world in adulthood as they were in adolescence. I then critique the idea, now almost de rigueur, that The Tenant of Wildfell Hall was written as a parody of Wuthering Heights. My conclusion is that by removing Charlotte Brontë's 'Biographical Notice' as a filter to our appreciation of Anne and Emily's literary partnership, it opens up new ways of engaging with their writing.